Vegetation composite material, method for preparing the same and use thereof

CN122940423APending Publication Date: 2026-10-20SHANXI INSTALLATION GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610900623.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

在强度(≥10MPa)、孔隙率(20%-30%)与低碱环境(pH≤9.0)之间,仍缺乏基于碳矿化结构调控的系统解决方案

Benefits of technology

[0044](1)在保证结构安全的前提下,实现了适宜植物生长的低碱环境构建。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention discloses a plant-based composite material, its preparation method, and its application, relating to the fields of ecological building materials and solid waste resource utilization. The plant-based composite material includes: (1) carbon mineralized structural aggregate, which, by weight, includes: 25-35 parts zeolite, 40-60 parts coal-based porous solid waste, 5-10 parts low-alkalinity sulfoaluminate cement, and 10-20 parts mineral active silica-alumina admixture; wherein, the coal-based porous solid waste is selected from one or more of coal gangue powder, fly ash, and coal gasification slag; and the mineral active silica-alumina admixture is selected from kaolin; (2) a cementitious matrix, which, by weight, includes: 40-50 parts coal-based porous solid waste, 20-30 parts low-alkalinity sulfoaluminate cement, 15-25 parts coal gasification slag, 1-3 parts chemical alkali reducing agent, and 0.2-0.5 parts polycarboxylate superplasticizer. This invention achieves synergistic improvements in engineering performance, ecological suitability, environmental safety, and carbon environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of ecological building materials and solid waste resource utilization, and in particular to a plant-based composite material, its preparation method, and its application. Background Technology

[0002] Slope protection technologies in transportation, water conservancy, mining, and municipal engineering are gradually shifting from traditional rigid support models towards green and low-carbon approaches. While traditional protection methods such as shotcrete and rockfill slope protection offer advantages in short-term structural stability, their material production processes involve high carbon emissions and resource consumption. Furthermore, the large-area hard cover layer formed after construction often weakens the slope's ecological restoration capacity, making it difficult to meet the comprehensive requirements of low-carbon and sustainable development in current engineering construction. Vegetated concrete, as an engineering material system that balances structural support and vegetation restoration, has received widespread attention in recent years and is gradually becoming an important direction for ecological slope management.

[0003] Coal mining, combustion, and gasification processes generate large quantities of coal-based solid waste, including coal gangue, fly ash, and coal gasification slag. These solid wastes generally contain active silica-alumina mineral phases and a certain proportion of calcareous components, theoretically possessing the potential to participate in hydration and carbon mineralization reactions. However, in existing concrete and vegetation concrete technologies, the application of coal-based solid waste is mostly limited to partially replacing cement or natural aggregates. Its functional positioning primarily focuses on cost reduction or resource utilization, without a systematic design approach for carbon mineralization reaction interfaces based on its mineral composition and porous structure advantages. The role of solid waste in material systems is more often that of passive filler or potentially active admixtures, rather than a core component actively participating in carbon reactions and structural construction.

[0004] Vegetated concrete, as an engineering material system that balances structural support and vegetation restoration, offers potential applications for the large-scale utilization of coal-based solid waste. By constructing a porous structure (with a porosity maintained at approximately 20%-30%), vegetated concrete provides the necessary space for plant root growth, water migration, and gas exchange, thus meeting the basic structural stability requirements for slope protection (28-day compressive strength generally not less than 8-12 MPa) and achieving a certain degree of integration between engineering structures and the natural ecosystem. However, in the process of evolving towards "green" and "high-performance" technologies, existing vegetated concrete technologies still mainly rely on traditional cement-based material systems, resulting in relatively singular raw material sources, high overall carbon emissions, and a generally high alkalinity within the material, with the pore solution pH often remaining above 10 for extended periods. Plant seed germination and root development are more suitable for a pH of 6.5-9.0. This significantly alkaline condition, deviating from the ecologically suitable range, creates obvious alkaline stress on plant germination and root growth. These problems, to some extent, restrict the widespread application of vegetated concrete in high-standard ecological restoration projects.

[0005] In terms of carbon emission control, traditional cement-based materials exhibit high carbon emission intensity per unit volume during the production stage, while during service, their carbonization process primarily relies on the natural diffusion of carbon dioxide from the environment. Due to the high density of the materials and the limited kinetics of the carbonization reaction, the natural carbonization depth is typically only a few millimeters, resulting in low carbon sequestration efficiency. Although the carbonization reaction can generate calcium carbonate to fill pores and reduce the alkalinity of the system to some extent, in existing planted concrete technologies, this process is usually considered a natural side reaction during long-term service and is not incorporated into the material structure design objectives, nor is it coordinated with pore structure construction, aggregate interface design, and cementitious system reaction processes. Therefore, in existing systems, carbonization is neither able to achieve effective engineering-scale carbon sequestration nor can it be transformed into an active means of structural reinforcement and alkalinity reduction.

[0006] Meanwhile, existing low-alkali regulation technologies often involve increasing the proportion of mineral admixtures to consume some calcium hydroxide or introducing acidic additives to achieve a phased pH reduction. However, these methods tend to focus on the chemical consumption process, lacking a holistic and coordinated design for the material's internal pore structure and carbon diffusion pathways. Furthermore, some alkali-reducing additives may adversely affect the material's hydration process and long-term durability, making it difficult to achieve a stable and controllable low-alkali environment on an engineering scale. Current technologies generally lack a systematic solution that can simultaneously address carbon mineralization enhancement, interface structure optimization, and active alkalinity regulation.

[0007] In summary, existing vegetation concrete for slope protection still primarily relies on traditional cement-based systems in its material and structural design, with coal-based solid waste often existing as substitute admixtures. A carbon mineralization enhancement mechanism centered on the mineral reaction interface has not yet been established. Alkalinity control mainly depends on passive blending or natural leaching processes, lacking a synergistic pathway for rapid alkalinity reduction and structural strengthening through controlled carbonization reactions. Furthermore, current technologies lack engineering design for the carbon sequestration potential during the material's service life, failing to transform the carbon sequestration process into a quantifiable and achievable structural optimization method. A systematic solution based on carbon mineralization-driven structural control is still lacking in addressing the balance between strength (≥10 MPa), porosity (20%-30%), and low-alkalinity environments (pH≤9.0). Summary of the Invention

[0008] To address the technical problems existing in the prior art, embodiments of the present invention provide a plant-based composite material, its preparation method, and its application. The technical solution is as follows:

[0009] A plant-based composite material, the plant-based composite material comprising:

[0010] (1) Carbon mineralized structural aggregate, by weight, comprising: 25-35 parts zeolite, 40-60 parts coal-based porous solid waste, 5-10 parts low-alkalinity sulfoaluminate cement, and 10-20 parts mineral active silica-alumina admixture; wherein, the coal-based porous solid waste is selected from one or more of coal gangue powder, fly ash, and coal gasification slag; and the mineral active silica-alumina admixture is selected from kaolin.

[0011] (2) Cementitious matrix, by weight, the cementitious matrix includes: 40-50 parts of coal-based porous solid waste, 20-30 parts of low-alkalinity sulfoaluminate cement, 15-25 parts of coal gasification slag, 1-3 parts of chemical alkali reducing agent, and 0.2-0.5 parts of polycarboxylate superplasticizer;

[0012] The carbon mineralized structural aggregate serves as the skeleton structure and accounts for 70%-80% of the total weight of the vegetation composite material; the low-alkali cementitious matrix serves as the cementing layer, wrapping the surface of the carbon mineralized structural aggregate and accounting for 20%-30% of the total weight of the vegetation composite material.

[0013] Optionally, the mineral-active silica-alumina admixture is selected from one or more of metakaolin, silica fume, or mechanically activated coal-derived kaolin, and its specific surface area is not less than 500 m². 2 / kg;

[0014] And / or, the pH value of the slurry of the low-alkalinity sulfoaluminate cement is not greater than 10.5 after 1 hour when the water-cement ratio is 1:10;

[0015] And / or, the zeolite is a natural or synthetic zeolite with a mesh size of 200 or larger and a purity of not less than 90%.

[0016] Optionally, the chemical alkali-reducing agent is selected from a mixture of oxalic acid and ferric sulfate in a mass ratio of 1:1 to 1:2.

[0017] Optionally, the amount of carbon-mineralized structural aggregate added accounts for 75% of the total weight of the vegetation composite material;

[0018] And / or, the amount of the low-alkali gelling matrix added accounts for 25% of the total weight of the vegetation composite material;

[0019] And / or, the carbonized structural aggregate is treated in a carbonization environment with a CO2 concentration of 10-20% before being mixed with the cementitious matrix;

[0020] And / or, the carbon mineralized structural aggregate is mixed with the cementitious matrix and then cured under conditions where the CO2 gas concentration is not less than 20%, thereby obtaining the plant-based composite material.

[0021] The method for preparing the aforementioned plant-based composite material includes:

[0022] (1) The components of the carbon mineralized structural aggregate are mixed evenly with water, molded, steam cured, and then transferred to a carbonization environment with a CO2 concentration of 10-20% for treatment, thereby obtaining the carbon mineralized structural aggregate.

[0023] (2) After the cementitious matrix is ​​mixed evenly with the carbon mineralized structural aggregate and water, it is molded and cured in two stages:

[0024] (a) Cur the molded specimens in a steam environment for 12-24 hours;

[0025] (b) The plant-based composite material is prepared by curing it for 3-7 days under conditions where the CO2 gas concentration is not less than 20%.

[0026] Optionally, in step (1), the weight ratio of water to carbon mineralized structural aggregate is 0.28-0.35;

[0027] And / or, in step (1), the molding is to produce wet aggregate with a particle size of 3-10 mm;

[0028] And / or, in step (1), the molding process is performed to produce the wet aggregate by granulation, light pressing or extrusion molding;

[0029] And / or, in step (1), the steam curing is to place the molded wet aggregate in an environment with a temperature of 40-60℃ and a relative humidity of ≥90% for low-temperature steam curing for 24-48 hours;

[0030] And / or, in step (1), the sample is treated in a carbonization environment for 12-24 hours;

[0031] And / or, in step (1), the degree of carbonization is controlled by an aggregate mass increase rate of 2-5%.

[0032] Optionally, in step (2), the water-to-glue ratio is controlled between 0.28 and 0.35;

[0033] And / or, in step (a), the steam environment is a saturated steam environment at 40-60°C;

[0034] And / or, in step (b), the ambient temperature is 20±5℃;

[0035] And / or, in step (b), the relative humidity is 60 ± 10%.

[0036] The application of the aforementioned vegetation composite material in the method of preparing vegetation concrete.

[0037] A type of vegetation concrete, wherein the vegetation concrete comprises the aforementioned vegetation composite material.

[0038] Optionally, the 28-day compressive strength of the vegetation concrete is ≥20 MPa;

[0039] And / or, the CO2 retention per unit volume of the vegetation concrete is ≥15 kg / m³. 3 ;

[0040] And / or, the alkalinity of the vegetation concrete is stable at 8.5-9.0.

[0041] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following:

[0042] This invention constructs a low-carbon vegetation composite material technology with carbon mineralization as the core structural strengthening mechanism, starting from the aspects of aggregate structure pretreatment, carbonization reaction control and interface mineralization synergy, so as to achieve the synergistic unity of high-value utilization of coal-based solid waste, active alkalinity regulation and structural enhancement.

[0043] Compared with existing vegetation concrete technology for slope protection, this invention constructs a low-alkali, low-carbon vegetation composite material system with carbon mineralized structural aggregates as the core, and introduces a hydration-carbonation synergistic curing mechanism. This achieves synergistic improvements in engineering performance, ecological suitability, environmental safety, and carbon environmental benefits. The specific technical effects are as follows:

[0044] (1) Under the premise of ensuring structural safety, a low-alkaline environment suitable for plant growth was constructed.

[0045] This invention effectively controls the alkalinity level of the pore solution in materials through the synergistic effect of low-alkalinity sulfoaluminate cement, coal-based solid waste mineral admixtures, composite chemical alkali-reducing agents, and enhanced carbonation curing. After synergistic curing, the pH value of the slurry inside the material can be stably reduced to below 9.0, which is significantly better than the long-term maintenance of pH ≥ 10 in traditional vegetated concrete. At the same time, it can still maintain a 28-day compressive strength of not less than 10 MPa, meeting the basic requirements of slope protection engineering for mechanical properties. This invention alleviates the alkali stress problem faced by plant germination and root growth from the material system level.

[0046] (2) A stable porous skeleton structure with carbon mineralized aggregate as the main body was constructed.

[0047] The carbon-mineralized structural aggregate, primarily composed of zeolite, coal-based solid waste, and coal-based porous solid waste, forms a stable porous framework structure through low-temperature steam curing. This framework then serves as the main load-bearing unit in the composite material, constructing a continuous pore network. This structure helps to stably control the overall porosity of the material within the range of 20%-30%, providing continuous space for plant root extension, water migration, and gas exchange. This improves vegetation emergence rate and medium- to long-term survival rate, transforming the ecological function of vegetated concrete from short-term improvement to long-term stable maintenance.

[0048] (3) High-value, hierarchical and safe utilization of coal-based solid waste has been achieved.

[0049] This invention introduces porous coal-based solid waste into carbon mineralization structural aggregates and low-alkali cementitious matrices, enabling it to participate in the carbon mineralization reaction and interface structure construction process. Compared to existing technologies that merely use it as a cement substitute or filler, this invention allows coal-based solid waste to undertake multiple functions in the material system, including porous structure construction, mineralization reaction interface formation, and alkalinity regulation, thereby enhancing the level of resource utilization. Simultaneously, the carbonization products have a certain encapsulating and stabilizing effect on potentially harmful components, helping to reduce long-term leaching risks and achieving a balance between resource utilization and environmental safety.

[0050] (4) Significantly enhances the carbon sequestration potential and carbon emission reduction benefits of the material system.

[0051] By incorporating an enhanced carbonation curing stage, this invention accelerates the diffusion and reaction rate of carbon dioxide within the material, allowing the carbon mineralization process to fully commence during the early structural formation stage. The generated carbonate minerals not only achieve stable carbon dioxide retention but also form a dense mineralization layer at the aggregate interface and in the pore structure, improving microstructural stability and synergistically reducing the system's alkalinity. Compared to traditional systems relying on natural carbonization, this invention achieves a synergistic coupling of carbon retention, interface strengthening, and alkalinity regulation, transforming carbonization from a passive process into an actively designed structural strengthening pathway.

[0052] (5) It has achieved synergistic optimization of engineering performance, ecological restoration function and carbon environmental benefits.

[0053] This invention, through the systematic coordination of material composition design, structural construction, and maintenance mechanism, enables vegetation concrete to meet the strength and stability requirements of slope protection engineering while simultaneously possessing a low-alkaline microenvironment suitable for plant growth, a stable porous structure, and considerable carbon sequestration potential. It breaks through the technical bottleneck of existing technologies that make it difficult to simultaneously achieve engineering performance, ecological function, and low-carbon goals, and has good engineering applicability and promotion value. Detailed Implementation

[0054] The technical solutions of the present invention will now be described in conjunction with specific embodiments.

[0055] In embodiments of the present invention, words such as "exemplarily," "for example," etc., are used to indicate that something is an example, illustration, or description. Any embodiment or design described as "exemplary" in the present invention should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of the word "exemplary" is intended to present the concept in a concrete manner. Furthermore, in embodiments of the present invention, the meaning expressed by "and / or" can be both, or either one.

[0056] To address the technical problems of existing planted concrete, such as high alkalinity, high carbon emission intensity, low utilization level of coal-based solid waste, and difficulty in synergizing ecological functions and engineering performance, this invention provides a low-carbon planted composite material based on carbon mineralized structural aggregate and its preparation method.

[0057] In a preferred embodiment of the present invention, the technical solution mainly includes two parts: the preparation of carbon mineralized structural aggregates and the mixing, molding and co-curing of composite materials, as detailed below.

[0058] 1. Preparation of carbon-mineralized structural aggregates

[0059] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 25-35 parts of zeolite powder, 40-60 parts of coal-based porous solid waste, 5-10 parts of low-alkalinity sulfoaluminate cement, and 10-20 parts of mineral active silica-alumina admixture.

[0060] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 30-50 rpm for 5-10 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 3-10 mm by granulation, light pressing or extrusion molding.

[0061] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 40-60℃ and a relative humidity of ≥90% for low-temperature steam curing for 24-48 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain granular carbon mineralized aggregate with a particle size of 3-10mm, which is then ready for use.

[0062] (4) Pre-carbonization and mineralization treatment: After steam curing, the aggregate is transferred to a carbonization environment with a CO2 concentration of 10-20% for 12-24 hours. During this stage, free Ca(OH)2 undergoes preliminary carbonization, and CaCO3 crystal nuclei are formed on the pore walls, providing active sites for subsequent carbonization reactions. After pre-carbonization, the aggregate is naturally cooled to room temperature to obtain carbon-mineralized aggregate. The existence of this stage transforms the aggregate from a hydrated porous body into a carbon reaction carrier with mineralization activity, which is significantly different from traditional ecological aggregates.

[0063] Furthermore, the zeolite powder mentioned in step 1 is natural or synthetic zeolite with a mesh size of 200 or larger and a purity of not less than 90%.

[0064] Furthermore, the coal-based porous solid waste mentioned in step 1 is selected from one or more of coal gangue powder, fly ash, and coal gasification slag;

[0065] Furthermore, in step 1, the low-alkalinity sulfoaluminate cement slurry has a pH value of no more than 10.5 after 1 hour when the water-cement ratio is 1:10.

[0066] Further, the mineral-active silica-alumina admixture mentioned in step 1 is selected from one or more of metakaolin, silica fume, or mechanically activated coal-derived kaolin, and its specific surface area is not less than 500 m². 2 / kg.

[0067] Furthermore, in step 1, the degree of pre-carbonization is controlled by an aggregate quality increase rate of 2-5%.

[0068] 2. Mixing, molding, and co-curing of composite materials

[0069] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made carbon mineralized structural aggregate; wherein the low-alkali cementitious matrix dry material is, by weight, 40-50 parts of coal-based porous solid waste, 20-30 parts of low-alkali sulfoaluminate cement, 15-25 parts of coal gasification slag fine powder, 1-3 parts of composite chemical alkali reducing agent, and 0.2-0.5 parts of polycarboxylate superplasticizer; wherein the carbon mineralized structural aggregate serves as the skeleton structure, and its addition accounts for 70%-80% of the total weight of the composite material; the low-alkali cementitious matrix serves as the cementing layer, coating the surface of the ecological aggregate, and its addition accounts for 20%-30% of the total weight of the composite material. The polycarboxylate superplasticizer is selected from commercially available standard products in powder form with a water reduction rate of not less than 25%;

[0070] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 2-3 minutes; then add the pre-made carbon mineralized structural aggregate and gently stir at a low speed of 15-30 rpm for 60-90 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed stirring state, slowly add the total mixing water (the water-cement ratio (the weight ratio of water to carbon mineralized structural aggregate) is controlled at 0.28-0.35), and then resume normal speed stirring for 3-5 minutes until the mixture forms a uniform composite slurry.

[0071] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30~45cm long, 30~45cm wide, 8~10cm high), and use a vibrating table to vibrate at low frequency for 10-30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0072] (4) Collaborative maintenance: It is divided into two consecutive stages, and the two stages are seamlessly connected:

[0073] Phase 1 (Early Hydration Curing): The molded specimens are moved to the curing chamber and cured in a saturated steam environment at 40-60℃ for 12-24 hours to promote the rapid hydration of low-alkali sulfoaluminate cement and coal-based solid waste, forming preliminary strength and specific pore structure.

[0074] Phase Two (Intensive Carbonation Curing): After demolding, the specimens are immediately transferred to a dedicated carbonation chamber. The environmental parameters inside the chamber are adjusted as follows: CO2 gas concentration not less than 20%, ambient temperature 20±5℃, and relative humidity 60±10%. Curing is carried out under these conditions for 3-7 days to complete the carbonation enhancement. By controlling the carbonation curing time and CO2 concentration, the pH value of the slurry is reduced to below 9.0 while preserving the mechanical integrity of the skeleton structure and preventing excessive decomposition of ettringite. In the intensive carbonation stage, CaCO3 crystal nuclei formed on the surface of the pre-carbonized aggregate serve as heterogeneous nucleation centers, accelerating the mineralization reaction in the slurry region and forming a continuous carbonate-reinforced transition layer.

[0075] Furthermore, the pH value of the low-alkalinity sulfoaluminate cement paste is ≤10.5 after 1 hour under a water-cement ratio of 1:10.

[0076] Furthermore, the composite chemical alkali-reducing agent mentioned in step 1 is a mixture of oxalic acid and ferric sulfate in a mass ratio of 1:1 to 1:2. It is mechanically mixed in a mixer at room temperature for 10-15 minutes until homogeneous, and then sealed and stored in a dry environment for later use. This composite chemical alkali-reducing agent is used to consume free calcium hydroxide in the early stages of material formation through complexation and precipitation reactions, and to provide a favorable chemical environment for subsequent carbonization curing.

[0077] Preferably, the compressive strength after carbonization is ≥20MPa after 28 days, and the CO2 retention per unit volume is ≥15kg / m³. 3 The alkalinity is stable at 8.5-9.0.

[0078] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with specific embodiments.

[0079] Unless otherwise specified, the experimental methods described in the following embodiments are conventional experimental methods well known to those skilled in the art, and are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Where specific conditions are not specified in the experimental methods, they are generally operated under conventional conditions.

[0080] Unless otherwise specified, all materials and reagents described in the following examples are commercially available.

[0081] Example 1: Preparation of low-carbon vegetation composite material 1 based on carbon mineralized structural aggregate

[0082] 1. Preparation of carbon-mineralized structural aggregates

[0083] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 25 parts of zeolite powder, 40 parts of coal-based porous solid waste, 5 parts of low-alkalinity sulfoaluminate cement, and 10 parts of mineral active silica-alumina admixture.

[0084] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 30 rpm for 5 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 5 mm by granulation, light pressing or extrusion molding.

[0085] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 40℃ and a relative humidity of ≥90% for low-temperature steam curing for 48 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain carbon mineralized aggregate for later use.

[0086] (4) Pre-carbonization and mineralization treatment: After steam curing, the aggregate is transferred to a carbonization environment with a CO2 concentration of 10% for 16 hours. During this stage, free Ca(OH)2 undergoes preliminary carbonization, and CaCO3 crystal nuclei are formed on the pore walls, providing active sites for subsequent carbonization reactions. After pre-carbonization, the aggregate is naturally cooled to room temperature to obtain carbon-mineralized aggregate. The existence of this stage transforms the aggregate from a hydrated porous body into a carbon reaction carrier with mineralization activity, which is significantly different from traditional ecological aggregates.

[0087] 2. Mixing, molding, and co-curing of composite materials

[0088] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made carbon mineralized structural aggregate; the low-alkali cementitious matrix dry material by weight is: 40 parts of coal-based porous solid waste, 20 parts of low-alkali sulfoaluminate cement, 15 parts of coal gasification slag fine powder, 1 part of composite chemical alkali reducing agent, and 0.2 parts of polycarboxylate water reducing agent; the carbon mineralized structural aggregate is used as the skeleton structure, and its addition accounts for 70% of the total weight of the composite material; the low-alkali cementitious matrix is ​​used as the cementing layer, wrapped on the surface of the ecological aggregate, and its addition accounts for 30% of the total weight of the composite material.

[0089] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 3 minutes; then add the pre-made carbon mineralized structural aggregate and gently mix at a low speed of 30 rpm for 90 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed mixing state, slowly add the total mixing water (the water-cement ratio is controlled at 0.28-0.30), and then restore the normal speed and mix for 5 minutes until the mixture forms a uniform composite slurry.

[0090] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0091] (4) Collaborative maintenance: It is divided into two consecutive stages, and the two stages are seamlessly connected:

[0092] Phase 1 (Early Hydration Curing): The molded specimens are moved to the curing chamber and cured in a saturated steam environment at 40°C for 24 hours to promote the rapid hydration of low-alkali sulfoaluminate cement and coal-based solid waste, forming preliminary strength and specific pore structure.

[0093] Phase Two (Intensive Carbonation Curing): After demolding, the specimens are immediately transferred to a dedicated carbonation chamber. The environmental parameters inside the chamber are adjusted to: CO2 gas concentration not less than 20%, ambient temperature 20±5℃, and relative humidity 60±10%. Curing is carried out under these conditions for 7 days to complete the carbonation enhancement. By controlling the carbonation curing time and CO2 concentration, the pH value of the slurry is reduced to below 9.0 while preserving the mechanical integrity of the skeleton structure and preventing excessive decomposition of ettringite. In the intensive carbonation stage, CaCO3 crystal nuclei formed on the surface of the pre-carbonized aggregate serve as heterogeneous nucleation centers, accelerating the mineralization reaction in the slurry region and forming a continuous carbonate-reinforced transition layer.

[0094] Example 2: Preparation of low-carbon vegetation composite material 2 based on carbon mineralized structural aggregate

[0095] 1. Preparation of carbon-mineralized structural aggregates

[0096] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 35 parts of zeolite powder, 60 parts of coal-based porous solid waste, 10 parts of low-alkalinity sulfoaluminate cement, and 20 parts of mineral active silica-alumina admixture.

[0097] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 50 rpm for 10 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 8 mm by granulation, light pressing or extrusion molding.

[0098] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 60℃ and a relative humidity of ≥90% for low-temperature steam curing for 48 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain carbon mineralized aggregate for later use.

[0099] (4) Pre-carbonization and mineralization treatment: After steam curing, the aggregate is transferred to a carbonization environment with a CO2 concentration of 20% for 24 hours. During this stage, free Ca(OH)2 undergoes preliminary carbonization, and CaCO3 crystal nuclei are formed on the pore walls, providing active sites for subsequent carbonization reactions. After pre-carbonization, the aggregate is naturally cooled to room temperature to obtain carbon-mineralized aggregate. The existence of this stage transforms the aggregate from a hydrated porous body into a carbon reaction carrier with mineralization activity, which is significantly different from traditional ecological aggregates.

[0100] 2. Mixing, molding, and co-curing of composite materials

[0101] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made carbon mineralized structural aggregate; the low-alkali cementitious matrix dry material by weight is: 50 parts of coal-based porous solid waste, 30 parts of low-alkali sulfoaluminate cement, 25 parts of coal gasification slag fine powder, 3 parts of composite chemical alkali reducing agent, and 0.5 parts of polycarboxylate water reducing agent; the carbon mineralized structural aggregate is used as the skeleton structure, and its addition accounts for 80% of the total weight of the composite material; the low-alkali cementitious matrix is ​​used as the cementing layer, wrapped on the surface of the ecological aggregate, and its addition accounts for 20% of the total weight of the composite material.

[0102] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 3 minutes; then add the pre-made carbon mineralized structural aggregate and gently mix at a low speed of 25 rpm for 60 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed mixing state, slowly add the total mixing water (the water-cement ratio is controlled at 0.32-0.35), and then restore the normal speed and mix for 5 minutes until the mixture forms a uniform composite slurry.

[0103] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 130 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0104] (4) Collaborative maintenance: It is divided into two consecutive stages, and the two stages are seamlessly connected:

[0105] Phase 1 (Early Hydration Curing): The molded specimens are moved to the curing chamber and cured in a saturated steam environment at 60°C for 20 hours to promote the rapid hydration of low-alkali sulfoaluminate cement and coal-based solid waste, forming preliminary strength and specific pore structure.

[0106] Phase Two (Intensive Carbonation Curing): After demolding, the specimens are immediately transferred to a dedicated carbonation chamber. The environmental parameters inside the chamber are adjusted to: CO2 gas concentration not less than 20%, ambient temperature 20±5℃, and relative humidity 60±10%. Curing is carried out under these conditions for 7 days to complete the carbonation enhancement. By controlling the carbonation curing time and CO2 concentration, the pH value of the slurry is reduced to below 9.0 while preserving the mechanical integrity of the skeleton structure and preventing excessive decomposition of ettringite. In the intensive carbonation stage, CaCO3 crystal nuclei formed on the surface of the pre-carbonized aggregate serve as heterogeneous nucleation centers, accelerating the mineralization reaction in the slurry region and forming a continuous carbonate-reinforced transition layer.

[0107] Example 3: Preparation of low-carbon vegetation composite material 3 based on carbon mineralized structural aggregate

[0108] 1. Preparation of carbon-mineralized structural aggregates

[0109] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 30 parts of zeolite powder, 50 parts of coal-based porous solid waste, 8 parts of low-alkalinity sulfoaluminate cement, and 15 parts of mineral active silica-alumina admixture.

[0110] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 45 rpm for 8 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 8 mm by granulation, light pressing or extrusion molding.

[0111] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 50℃ and a relative humidity of ≥90% for low-temperature steam curing for 36 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain carbon mineralized aggregate for later use.

[0112] (4) Pre-carbonization and mineralization treatment: After steam curing, the aggregate is transferred to a carbonization environment with a CO2 concentration of 15% for 24 hours. During this stage, free Ca(OH)2 undergoes preliminary carbonization, and CaCO3 crystal nuclei are formed on the pore walls, providing active sites for subsequent carbonization reactions. After pre-carbonization, the aggregate is naturally cooled to room temperature to obtain carbon-mineralized aggregate. The existence of this stage transforms the aggregate from a hydrated porous body into a carbon reaction carrier with mineralization activity, which is significantly different from traditional ecological aggregates.

[0113] 2. Mixing, molding, and co-curing of composite materials

[0114] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made carbon mineralized structural aggregate; the low-alkali cementitious matrix dry material by weight is: 45 parts of coal-based porous solid waste, 25 parts of low-alkali sulfoaluminate cement, 20 parts of coal gasification slag fine powder, 2 parts of composite chemical alkali reducing agent, and 0.3 parts of polycarboxylate water reducing agent; the carbon mineralized structural aggregate is used as the skeleton structure, and its addition accounts for 75% of the total weight of the composite material; the low-alkali cementitious matrix is ​​used as the cementing layer, wrapped on the surface of the ecological aggregate, and its addition accounts for 25% of the total weight of the composite material.

[0115] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 3 minutes; then add the pre-made carbon mineralized structural aggregate and gently mix at a low speed of 25 rpm for 90 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed mixing state, slowly add the total mixing water (the water-cement ratio is controlled at 0.30-0.32), and then resume normal speed mixing for 5 minutes until the mixture forms a uniform composite slurry.

[0116] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0117] (4) Collaborative maintenance: It is divided into two consecutive stages, and the two stages are seamlessly connected:

[0118] Phase 1 (Early Hydration Curing): The molded specimens are moved to the curing chamber and cured in a saturated steam environment at 50°C for 36 hours to promote the rapid hydration of low-alkali sulfoaluminate cement and coal-based solid waste, forming preliminary strength and specific pore structure.

[0119] Phase Two (Enhanced Carbonation Curing): After demolding, the specimens are immediately transferred to a dedicated carbonation chamber. The environmental parameters inside the chamber are adjusted as follows: CO2 gas concentration not less than 20%, ambient temperature 20±5℃, and relative humidity 60±10%. Under these conditions, the specimens are cured for 3-7 days to complete the enhanced carbonation. By controlling the carbonation curing time and CO2 concentration, the pH value of the slurry is reduced to below 9.0 while preserving the mechanical integrity of the skeleton structure and preventing excessive decomposition of ettringite.

[0120] Comparative Example 1: Structural aggregate system without pre-carbonization treatment

[0121] 1. Aggregate preparation

[0122] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 25 parts of zeolite powder, 50 parts of low-alkalinity sulfoaluminate cement, and 10 parts of mineral active silica-alumina admixture.

[0123] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 50 rpm for 10 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 8 mm by granulation, light pressing or extrusion molding.

[0124] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 40℃ and a relative humidity of ≥90% for low-temperature steam curing for 48 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain carbon mineralized aggregate for later use.

[0125] 2. Mixing, molding, and co-curing of composite materials

[0126] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made aggregate; the low-alkali cementitious matrix dry material by weight is: 60 parts of low-alkali sulfoaluminate cement, 15 parts of coal gasification slag fine powder, 1 part of composite chemical alkali reducing agent, and 0.2 parts of polycarboxylate superplasticizer; the aggregate serves as the skeleton structure, and its addition accounts for 70% of the total weight of the composite material; the low-alkali cementitious matrix serves as the cementing layer, wrapping the surface of the ecological aggregate, and its addition accounts for 30% of the total weight of the composite material.

[0127] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 3 minutes; then add the pre-made carbon mineralized structural aggregate and gently mix at a low speed of 30 rpm for 90 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed mixing state, slowly add the total mixing water (the water-cement ratio is controlled at 0.32-0.35), and then restore the normal speed and mix for 5 minutes until the mixture forms a uniform composite slurry.

[0128] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0129] (4) Collaborative maintenance: It is divided into two consecutive stages, and the two stages are seamlessly connected:

[0130] Phase 1 (Early Hydration Curing): The molded specimens are moved to the curing chamber and cured in a saturated steam environment at 40-60℃ for 12-24 hours to promote the rapid hydration of low-alkali sulfoaluminate cement and coal-based solid waste, forming a porous structure.

[0131] Phase Two (Intensive Carbonation Curing): After demolding, the specimens are immediately transferred to a dedicated carbonation chamber. The environmental parameters inside the chamber are adjusted as follows: CO2 gas concentration not less than 20%, ambient temperature 20±5℃, and relative humidity 60±10%. Curing is carried out under these conditions for 3-7 days to complete the carbonation enhancement. By controlling the carbonation curing time and CO2 concentration, the pH value of the slurry is reduced to below 9.0 while preserving the mechanical integrity of the skeleton structure and preventing excessive decomposition of ettringite. In the intensive carbonation stage, CaCO3 crystal nuclei formed on the surface of the pre-carbonized aggregate serve as heterogeneous nucleation centers, accelerating the mineralization reaction in the slurry region and forming a continuous carbonate-reinforced transition layer.

[0132] Comparative Example 2: System without enhanced carbonization curing

[0133] 1. Aggregate preparation

[0134] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 25 parts of zeolite powder, 50 parts of low-alkalinity sulfoaluminate cement, and 10 parts of mineral active silica-alumina admixture.

[0135] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 50 rpm for 10 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet carbon mineralized structural aggregate with a particle size of 8 mm by granulation, light pressing or extrusion molding.

[0136] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 40℃ and a relative humidity of ≥90% for low-temperature steam curing for 48 hours. Steam curing promotes the initial hydration reaction of low-alkalinity sulfoaluminate cement, forming a stable porous skeleton structure inside the aggregate and enhancing the interfacial bonding between zeolite, mineral admixtures and coal-based solid waste. After curing, it is naturally cooled to room temperature to obtain carbon mineralized aggregate for later use.

[0137] (4) Pre-carbonization and mineralization treatment: After steam curing, the aggregate is transferred to a carbonization environment with a CO2 concentration of 15% for 24 hours. During this stage, free Ca(OH)2 undergoes preliminary carbonization, and CaCO3 crystal nuclei are formed on the pore walls, providing active sites for subsequent carbonization reactions. After pre-carbonization, the aggregate is naturally cooled to room temperature to obtain carbon-mineralized aggregate. The existence of this stage transforms the aggregate from a hydrated porous body into a carbon reaction carrier with mineralization activity, which is significantly different from traditional ecological aggregates.

[0138] 2. Mixing, molding, and co-curing of composite materials

[0139] (1) Raw material preparation: Prepare low-alkali cementitious matrix dry material and the above-mentioned pre-made aggregate; the low-alkali cementitious matrix dry material by weight is: 60 parts of low-alkali sulfoaluminate cement, 15 parts of coal gasification slag fine powder, 1 part of composite chemical alkali reducing agent, and 0.2 parts of polycarboxylate superplasticizer; the aggregate serves as the skeleton structure, and its addition accounts for 70% of the total weight of the composite material; the low-alkali cementitious matrix serves as the cementing layer, wrapping the surface of the ecological aggregate, and its addition accounts for 30% of the total weight of the composite material.

[0140] (2) Feeding and mixing: First, put all the dry materials of the low-alkali cementitious matrix into the mixer and dry mix for 3 minutes; then add the pre-made carbon mineralized structural aggregate and gently mix at a low speed of 30 rpm for 90 seconds to ensure that the aggregate is evenly dispersed and not damaged; under the continuous low speed mixing state, slowly add the total mixing water (the water-cement ratio is controlled at 0.32-0.35), and then restore the normal speed and mix for 5 minutes until the mixture forms a uniform composite slurry.

[0141] (3) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0142] (4) Co-curing: After molding, the specimens are moved to the curing room and cured in a saturated steam environment of 40-60℃ for 12-24 hours to promote the rapid hydration of low alkali sulfoaluminate cement and coal-based solid waste and form a porous structure.

[0143] Comparative Example 3: Traditional Vegetated Concrete System

[0144] 1. Aggregate preparation

[0145] (1) Raw material preparation: Prepare the following dry base raw materials by weight: 50 parts of coal-based porous solid waste and 50 parts of low-alkalinity sulfoaluminate cement.

[0146] (2) Dry mixing and molding: Put all the above powdered raw materials into a high-efficiency forced mixer and dry mix at a speed of 45 rpm for 8 minutes to ensure uniform mixing. Then add an appropriate amount of mixing water to the mixture to form a plastic wet material, and prepare wet aggregate with a particle size of 8 mm by granulation, light pressing or extrusion molding.

[0147] (3) Aggregate curing: The molded wet aggregate is placed in an environment with a temperature of 50℃ and a relative humidity of ≥90% for low-temperature steam curing for 36 hours. After curing, it is naturally cooled to room temperature to obtain carbon mineralized structural aggregate for later use.

[0148] (4) Molding: Pour the well-stirred composite slurry into the pre-set mold (30cm long, 30cm wide, and 8cm high), and use a vibrating table to vibrate at low frequency for 30 seconds to remove air bubbles inside the slurry and ensure that the molding is dense.

[0149] (5) Co-curing: The molded specimens were moved to the curing room and cured in a saturated steam environment at 50°C for 36 hours.

[0150] Experiment 1 Performance Testing

[0151] Performance tests were performed on Examples 1-3 and Comparative Examples 1-3 according to the following standards and methods:

[0152] Pore ​​liquid phase pH value: According to GB / T176-2017 "Chemical Analysis Methods for Cement", the deionized water immersion method was used for testing;

[0153] 28-day compressive strength: Tested according to GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)";

[0154] Carbon sequestration: The amount of CO2 fixed per unit volume of material is calculated using the gravimetric method.

[0155] .

[0156] In the formula: W 105 W 550 and W 850 The values ​​are the mass of the material after being heated to 105℃, 500℃, and 850℃, respectively.

[0157] Plant adaptability: Germination test was conducted using ryegrass seeds. The seeds were cultured for 7 days at 25℃ and 70% humidity, and the germination rate was recorded.

[0158] Experimental results:

[0159] The experimental results are shown in Table 1.

[0160] Table 1 Sample performance test results

[0161]

[0162] As shown in Table 1, the test results demonstrate that the composite material prepared by this patent is significantly superior to the comparative example prepared using conventional techniques in terms of alkalinity control, mechanical strength, carbon fixation capacity, and vegetation adaptability, exhibiting outstanding technical effects. The porosity of Examples 1-3 remains at a high level of 35.79%~38.77%, significantly higher than the comparative example (21.47%~28.64%). Under these high porosity conditions, the 28-day compressive strength of the examples still reaches 9.7~12.4 MPa, superior to the 5.9~7.3 MPa of the comparative example. The data indicate that the carbon mineralized structural aggregate and its curing process of this invention effectively solve the problem of a sharp drop in strength caused by high porosity in vegetation concrete, meeting the structural requirements for slope protection. The pH value of the pore solution in Examples 1-3 is effectively controlled between 9.2 and 9.4, lower than the 10.2~11.8 of the comparative example. The 7-day germination rate of ryegrass in the examples reached 80.4%~86.3%, while the germination rate of the conventional formulation in Comparative Example 3 was only 3.57%. The inventors speculate that this may be due to, for example, a low-alkaline environment. The above data demonstrate that the present invention, through the synergistic effect of alkali-reducing agents and carbonization maintenance, successfully relieves the strong alkaline stress faced by plants and significantly improves their adaptability. The 48-hour carbon sequestration per unit volume in Examples 1-3 reached 5.74~6.27 kg / m³. 3 Approximately the comparative ratio (2.74~3.57 kg / m³). 3 The data shows that using coal-based porous solid waste as a carrier, combined with pre-carbonization and enhanced carbonization processes, can significantly increase the absorption and storage capacity of carbon dioxide in composite materials, achieving remarkable carbon sequestration and emission reduction effects.

[0163] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A plant-based composite material, characterized in that, The plant-based composite material includes: (1) Carbon mineralized structural aggregate, by weight, comprising: 25-35 parts zeolite, 40-60 parts coal-based porous solid waste, 5-10 parts low-alkalinity sulfoaluminate cement, and 10-20 parts mineral active silica-alumina admixture; wherein, the coal-based porous solid waste is selected from one or more of coal gangue powder, fly ash, and coal gasification slag; and the mineral active silica-alumina admixture is selected from kaolin. (2) Cementitious matrix, by weight, the cementitious matrix includes: 40-50 parts of coal-based porous solid waste, 20-30 parts of low-alkalinity sulfoaluminate cement, 15-25 parts of coal gasification slag, 1-3 parts of chemical alkali reducing agent, and 0.2-0.5 parts of polycarboxylate superplasticizer; The carbon mineralized structural aggregate serves as the skeleton structure and accounts for 70%-80% of the total weight of the vegetation composite material; the low-alkali cementitious matrix serves as the cementing layer, wrapping the surface of the carbon mineralized structural aggregate and accounting for 20%-30% of the total weight of the vegetation composite material.

2. The plant-based composite material according to claim 1, characterized in that, The mineral-active silica-alumina admixture is selected from one or more of metakaolin, silica fume, or mechanically activated coal-derived kaolin, and its specific surface area is not less than 500 m². 2 / kg; And / or, the pH value of the slurry of the low-alkalinity sulfoaluminate cement is not greater than 10.5 after 1 hour when the water-cement ratio is 1:10; And / or, the zeolite is a natural or synthetic zeolite with a mesh size of 200 or larger and a purity of not less than 90%.

3. The plant-based composite material according to claim 1, characterized in that, The chemical alkali-reducing agent is selected from a mixture of oxalic acid and ferric sulfate in a mass ratio of 1:1 to 1:

2.

4. The plant-based composite material according to claim 1, characterized in that, The amount of carbon-mineralized structural aggregate added accounts for 75% of the total weight of the plant composite material; And / or, the amount of the low-alkali gelling matrix added accounts for 25% of the total weight of the vegetation composite material; And / or, the carbonized structural aggregate is treated in a carbonization environment with a CO2 concentration of 10-20% before being mixed with the cementitious matrix; And / or, the carbon mineralized structural aggregate is mixed with the cementitious matrix and then cured under conditions where the CO2 gas concentration is not less than 20%, thereby obtaining the plant-based composite material.

5. The method for preparing the plant-based composite material according to any one of claims 1-4, characterized in that, The preparation method includes: (1) The components of the carbon mineralized structural aggregate are mixed evenly with water, molded, steam cured, and then transferred to a carbonization environment with a CO2 concentration of 10-20% for treatment, thereby obtaining the carbon mineralized structural aggregate. (2) After the cementitious matrix is ​​mixed evenly with the carbon mineralized structural aggregate and water, it is molded and cured in two stages: (a) Cur the molded specimens in a steam environment for 12-24 hours; (b) The plant-based composite material is prepared by curing it for 3-7 days under conditions where the CO2 gas concentration is not less than 20%.

6. The preparation method according to claim 5, characterized in that, In step (1), the weight ratio of water to carbon mineralized structural aggregate is 0.28-0.35; And / or, in step (1), the molding is to produce wet aggregate with a particle size of 3-10 mm; And / or, in step (1), the molding process is performed to produce the wet aggregate by granulation, light pressing or extrusion molding; And / or, in step (1), the steam curing is to place the molded wet aggregate in an environment with a temperature of 40-60℃ and a relative humidity of ≥90% for low-temperature steam curing for 24-48 hours; And / or, in step (1), the sample is treated in a carbonization environment for 12-24 hours; And / or, in step (1), the degree of carbonization is controlled by an aggregate mass increase rate of 2-5%.

7. The preparation method according to claim 5, characterized in that, In step (2), the water-to-glue ratio is controlled between 0.28 and 0.35; And / or, in step (a), the steam environment is a saturated steam environment at 40-60°C; And / or, in step (b), the ambient temperature is 20±5℃; And / or, in step (b), the relative humidity is 60 ± 10%.

8. The use of the vegetation composite material according to any one of claims 1-4 in the method of preparing vegetation concrete.

9. A type of plant-based concrete, characterized in that, The vegetation concrete includes the vegetation composite material according to any one of claims 1-4.

10. The vegetation concrete according to claim 9, characterized in that, The 28-day compressive strength of the planted concrete is ≥20MPa; And / or, the CO2 retention per unit volume of the vegetation concrete is ≥15 kg / m³. 3 ; And / or, the alkalinity of the vegetation concrete is stable at 8.5-9.0.